2019
DOI: 10.1002/ajb2.1375
|View full text |Cite
|
Sign up to set email alerts
|

Autopolyploidy alters nodule‐level interactions in the legumerhizobium mutualism

Abstract: Premise Polyploidy is a major genetic driver of ecological and evolutionary processes in plants, yet its effects on plant interactions with mutualistic microbes remain unresolved. The legume–rhizobium symbiosis regulates global nutrient cycles and plays a role in the diversification of legume species. In this mutualism, rhizobia bacteria fix nitrogen in exchange for carbon provided by legume hosts. This exchange occurs inside root nodules, which house bacterial cells and represent the interface of legume–rhizo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 127 publications
1
22
0
Order By: Relevance
“…Furthermore, although not tested directly here, a separate analysis of internal nodule traits of diploid and neotetraploid M. sativa subsp. caerulea found that polyploidy directly increased the size of rhizobia (bacteroids) hosted within nodules (Forrester & Ashman, 2019), a metric positively correlated with the amount of N provided to plant hosts (Oono & Denison, 2010). Thus, multiple mechanisms may have led to the polyploid advantage observed here.…”
Section: Discussionmentioning
confidence: 64%
See 3 more Smart Citations
“…Furthermore, although not tested directly here, a separate analysis of internal nodule traits of diploid and neotetraploid M. sativa subsp. caerulea found that polyploidy directly increased the size of rhizobia (bacteroids) hosted within nodules (Forrester & Ashman, 2019), a metric positively correlated with the amount of N provided to plant hosts (Oono & Denison, 2010). Thus, multiple mechanisms may have led to the polyploid advantage observed here.…”
Section: Discussionmentioning
confidence: 64%
“…Comparing established diploid and polyploid plants of the same species provides insight into how polyploidy might impact the evolutionary trajectory of plant species in natural populations (Spoelhof et al, 2017;Baduel et al, 2018;Forrester & Ashman, 2019). Medicago experienced multiple polyploidization events throughout its history, including an event 58 million years ago (Cannon et al, 2006;Young et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While natural polyploids have been used to investigate evolutionary and ecological questions including ecological niche differentiation, defense against herbivores, and stress tolerance [72][73][74][75][76][77], the production of synthetic allopolyploids allows for the study of traits instantaneously after genome merger. Many recent papers have used synthetic polyploids to study functional traits and inflorescence morphology in a variety of species [78][79][80][81][82][83]. By comparing natural and synthetic polyploids, the immediate consequences of polyploidy can be disentangled from the changes that occur via subsequent evolution following whole genome duplication.…”
Section: Introductionmentioning
confidence: 99%